Aplastic Anemia & MDS International Foundation (AA&MDSIF): Bone Marrow Failure Disease Scientific Symposium 2018. (May 2019) - Becktell, Kerri; Berlyne, Deborah; Pagliuca, Simona; Pommert, Lauren; Prata, Pedro H.; Margolis, David; de Latour, Régis Peffault; Dufour, Carlo; Pierri, Filomena
Abstract: The bone marrow failure (BMF) syndromes are a group of rare disorders characterized by ineffective hematopoiesis resulting from deficiencies in the hematopoietic stem cell compartment. Although these diseases are typically acquired, some forms (e.g., Fanconi anemia, dyskeratosis congenita, Diamond Blackfan anemia, and Shwachman Diamond syndrome) are inherited. Patients with BMF syndromes can develop peripheral blood cytopenias and pancytopenia, and their disease can ultimately progress to acute myelogenous leukemia (AML). Research around the world is shedding light on the biology of the BMF syndromes, their clinical effects, and novel treatments. The Aplastic Anemia and MDS International Foundation (AAMDSIF) is an independent nonprofit organization whose mission is to help patients and family members cope with BMF syndromes. This report summarizes presentations on the latest scientific discoveries in BMF syndromes from the Sixth International Bone Marrow Failure Disease Scientific Symposium sponsored by AAMDSIF on March 22–23, 2018, in Rockville, Maryland.